Pre-opereative Parathormone Levels are Correlated with Mean Diameter of Parathyroid Adenoma and Pre-operative Serum Calcium and Alkaline Phosphatase Levels - Gulsah Elbuken; Recep Aktimur; Kadir Yildirim; Sude Hatun Aktimur; Mehmet Derya Demirag; Aysu Basak Ozbalci; Mustafa Bakirtas; Banu Kirtiloglu; Nuraydin Ozlem (Medicine Science, 2015)
The aim of the present study was to determine the relationship between biochemical parameters, mean diameter of parathyroid adenoma (MDPA) and parathyroid hormone (PTH) levels in patients who underwent parathyroid surgery.Materials and Methods: Data were collected retrospectively from patients with hyperparathyroidism who were operated and followed in our hospital between September 2011 and April 2014. Twenty-nine (male/female = 8/21) patients with a mean age of 58.31 ± 12.59 years were enrolled into the study. The mean pre-operative serum calcium and intact PTH (iPTH) levels were 11.98±1.23 mg/dl and 386.52±374.96 pg/ml, respectively. Serum pre-operative calcium levels were found to be significantly higher in patients who had nephrolithiasis than those who did not, whereas pre-operative serum phosphate levels were lower. Pre-operative iPTH levels were found to be correlated with pre-operative calcium, alkaline phosphatase and MDPA but not with pre-operative serum phosphate. Also, pre-operative calcium levels were found to be significantly correlated with MDPA.Conclusion: Presence of nephrolithiasis is associated with higher pre-operative calcium and lower phosphate levels. Pre-operative iPTH and calcium levels were also found to be significantly correlated with MDPA; this suggests that serum iPTH and calcium levels can be useful in predicting MDPA. [Med-Science 2015; 4(3.000): 2401-13]